Analysis of the Quality Stability of Strawberry Juice Fermented with Water Kefir Grains during Refrigeration - Linlin YIN; Zhina CHEN; Ruixue SUN; Xianya LIU; Yuxin WANG (Shipin gongye ke-ji)
To investigate the quality stability of strawberry juice fermented with water kefir grains during refrigeration. Variations in the primary physical and chemical parameters were analyzed, together with analysis of the active compounds, antioxidant capacity, viable bacterial and yeast counts, and sensory attributes of the fermented strawberry juice over a 28 day refrigeration period at 4 ℃. Results showed that during refrigeration, the total phenol, total flavonoid, and vitamin C contents in the fermented strawberry juice decreased. Correspondingly, the antioxidant capacity, including the activity of superoxide dismutase and the DPPH and ABTS+ free radical-scavenging rates were reduced by 16%, 8.5%, and 28.3%, respectively. The viable lactic acid bacterial and yeast counts decreased by 12.8% and 14%, respectively, while the counts of viable acetic acid bacteria increased by 16%. In the sensory evaluation, in addition to the observed increase in the odor score, the color score of the fermented strawberry juice decreased due to reductions in the L* and a* values and an increase in the b* value. At the same time, reductions in the suspension stability and pH also led to lower scores for texture and taste, however, these scores still remained above 6 points. During refrigeration, the main physical and chemical indicators, as well as the levels of active substances, in the strawberry juice fermented with water kefir grains, were found to be relatively stable. The number of viable lactic acid bacteria was above 6 lg CFU/mL, while the antioxidant capacity remained at a high level of more than 65%. In addition, the results of the sensory evaluation fell within the acceptable range. These findings indicated that the overall quality of water kefir grains-fermented strawberry juice remained stable over 28 days of refrigeration.